The greatest knight the remarkable life of William Marshal, the power behind five English thrones - Asbridge, Thomas S. 1969- (Ecco, 2014)
The story of the largely forgotten William Marshal Pembroke of the English medieval period, who, "as a five-year-old boy ... was sentenced to execution and led to the gallows, yet this landless younger son survived his brush with death, and went on to train as a medieval knight. Against all odds, [he] rose through the ranks--serving at the right hand of five English monarchs--to become a celebrated tournament champion, a baron and politician and, ultimately, regent of the realm"--Amazon.com